Timber pests and diseases - Findlay, W. P. K. (Walter Philip Kennedy) (Pergamon series of monographs on furniture and timber, 1967)
Timber Pests and Diseases is an updated version of an earlier work entitled Dry Rot and Other Timber Troubles, which is out of print. The opportunity was taken to revise the text throughout, bringing it up to date and including the results of recent research work. A new chapter on Termites has been included. Detailed reference to wood preservatives has been omitted as modern works dealing with this subject have recently been published. The book begins with a discussion of the economic impact of timber pests and disease. Separate chapters cover the nature of wood; the causes of deterioration in.